The Role of Higher Education for Sustainable Development Goals: Experiences from Mahidol University, Thailand - Mahaisavariya, Banchong; Charmondusit, Kitikorn (Universitas Diponegoro, 2023)
Higher education is one of the significant stakeholder to play an important role in fostering sustainable development goals. Mahidol University is a comprehensive university in Thailand, which strives to be a leader on sustainability in responding to the United Nation 2030 agenda for sustainable development goals. Therefore, Mahidol University sustainability strategy, which consists of 4 key areas as a framework including 1) research and innovation for sustainability 2) education for sustainability 3) community and social engagement for sustainability 4) operations for sustainability was established. The implementation of Mahidol University sustainability strategy demonstrates many successful activity programs, which can be a robust model to other university.